Change in uterine artery blood flow with intrauterine balloon tamponade - Ryuichi Shimaoka; Tomomi Shiga; Ken-ichirou Morishige (IMR Press, 2021)
The purpose of this study was to investigate the change in uterine artery blood flow in cases of intrauterine balloon tamponade (IBT). This was a retrospective cross-sectional study of 132 patients who underwent singleton cesarean section. IBT was performed in 35 of the 132 patients. There were 21 cases of placental mediated pregnancy complications (PMPC), which were not included in the IBT group. Placental positional abnormalities were significantly more common in the IBT group than in the control group (89% vs. 9%, P < 0.001). Multivariate analysis identified PMPC as a factor affecting the immediate preoperative uterine artery pulsatility index (UtA-PI). Finally, PMPC was excluded and we assessed 35 and 76 patients assigned to the IBT and control groups, respectively. We compared changes in uterine artery blood flow with and without IBT and by balloon volume. In the IBT group, the immediate pre- and postoperative UtA-PIs were significantly lower (0.56 ± 0.18 vs. 0.63 ± 0.15, P = 0.011, statistical power = 0.577) and higher (1.37 ± 0.66 vs. 0.96 ± 0.28, P < 0.001, statistical power = 0.986), respectively, than those in the control group. The immediate postoperative UtA-PIs depending on balloon expansion volume were 1.13 ± 0.60, 1.24 ± 0.57, and 1.71 ± 0.75, with balloon volumes of 100-199 mL, 200-299 mL, and 300-399 mL, respectively. In summary, IBT during cesarean section increases the immediate post-operative UtA-PI, and tends to increase with increase in balloon volume.